Features of Primary Ocular Disability in the Krasnodar Region in 2016–2018 - A. S. Apostolova; A. V. Malyshev; A. A. Bashko; A. A. Sergienko; E. V. Kudryavceva (Oftalʹmologiâ)
Purpose: to study the state and dynamics of changes in primary ocular disability in the period 2016–2018 by nosological forms. A complete retrospective study was made based on the data of the MSE (medical and social expertise) Bureau’s reporting documents. The following indicators of primary disability (per 10 thousand population) were registered from 2016 till 2018: among the adult population (18 years and older) 69,0–70,7–68,6 respectively; among the able-bodied population 42,8–44,1–41,1 respectively; among the population of retirement age — 125,1–126,4–124,6 accordingly. In the structure of primary disability of the adult population by severity for the period 2016–2018, the dynamics recorded an increase in the proportion of 1 group and 3 group with a decrease in the share of disability of 2 group. In the nosological structure of primary disability of the adult population in 2016–2017–2018, eye diseases account for 3 %, 3 % and 3.2 %, respectively, of all first recognized as disabled. There has been an increase in first-time applicants to the MSE Bureau. In the nosological structure of primary disability, the percentage of glaucoma patients over the past period is 47–33–32.5 % of the total number of primary disability for eye diseases, which determines the 1st rank. There is a progressive increase in the number of people with disabilities due to glaucoma of group 1 and group 2 throughout the study period. In the nosological structure of primary disability for 2016–2018 the percentage of patients with retinal diseases is 25–23–23.8 % of the total number of primary disability for eye diseases, which corresponds to the 2nd rank. There is a progressive increase in the number of disabled people in group 2. A low proportion of persons of working age in the structure of primary ocular disability was noted. A consistently high share of primary disability and a progressive increase in severe disability combined with an increase in persons of retirement age in the Krasnodar region forms an unfavorable forecast for an increase in the number of blind and visually impaired residents of the region.